Penerapan Metode Sobel Edge Detection dan Image Processing Untuk Mengetahui Diameter Apel Fuji Menggunakan Aplikasi Matlab - Hasibuan, Alima Hakkon; Zebua, Taronisokhi; Hondro, Rivalri Kristianto (JURIKOM (Jurnal Riset Komputer), 2020)
Fuji apples (Malus Domestika) are fruits that contain a lot of antioxidants. Besides the fruit flesh, the apple also contains pectin. Fuji apples are red and have a yellow line. The size of apples can affect the selling price of apples, the determination of the size of apples can be seen from the size of the diameter, measuring the diameter of apples is usually done visually by comparing apples. Based on these problems, a research is needed to develop a system to determine the diameter of fuji apples by using image processing techniques to find the diameter. This measurement process uses the matlab application and tests with the sobel edge detection method and image processing to see the more visible edges of the lines. The results showed that the developed system was able to obtain images and identify the diameter of fuji apples